Reflections on COVID-19 and how to prevent future pandemics - Carroll, D.; Smith, Jimmy W. (International Livestock Research Institute, 2020)
Dennis Carroll, chair of the Global Virome Project Leadership Board and former director of the United States Agency for International Development's Pandemic Influenza and other Emerging Threats Unit, shared his reflections on COVID-19 and how we can prevent future pandemics at an online town hall meeting of the International Livestock Research Institute (ILRI) on 18 September 2020. Carroll described the scale of the initiatives needed to counter the emergence of global pandemics and regretted the world’s failure to take the threat as seriously as it should have done.